Eda controls the size of the enamel knot during incisor development - Horakova, Lucie; Dalecka, Linda; Zahradnicek, Oldrich; Lochovska, Katerina; Lesot, Herve; Peterkova, Renata; Tucker, Abigail S.; Hovorakova, Maria (Frontiers in Physiology, 2023)
Ectodysplasin (Eda) plays important roles in both shaping the developing tooth and establishing the number of teeth within the tooth row. Sonic hedgehog (Shh) has been shown to act downstream of Eda and is involved in the initiation of tooth development. Eda−/− mice possess hypoplastic and hypomineralized incisors and show changes in tooth number in the molar region. In the present study we used 3D reconstruction combined with expression analysis, cell lineage tracing experiments, and western blot analysis in order to investigate the formation of the incisor germs in Eda−/− mice. We show that a lack of functional Eda protein during early stages of incisor tooth germ development had minimal impact on development of the early expression of Shh in the incisor, a region proposed to mark formation of a rudimental incisor placode and act as an initiating signalling centre. In contrast, deficiency of Eda protein had a later impact on expression of Shh in the primary enamel knot of the functional tooth. Eda−/− mice had a smaller region where Shh was expressed, and a reduced contribution from Shh descendant cells. The reduction in the enamel knot led to the formation of an abnormal enamel organ creating a hypoplastic functional incisor. Eda therefore appears to influence the spatial formation of the successional signalling centres during odontogenesis.